Improving outcome in perforated peptic ulcer emergency surgery by Boey scoring - Gulzar, Jasneet Singh; Paruthy, Shivani B.; Arya, Satya Vrat (International Surgery Journal, 2016)
Background: since perforation occurs in 2% of patients of peptic ulcer disease hence perforated peptic ulcer is one of the most common indications for emergency gastrointestinal surgery. Delayed treatment, older age, presence of shock on admission and American Society of Anesthetisiologist status (ASA) are the risk factors for prediction of complication and mortality. A delay of more than 24 hours increases the lethal status seven to eight fold and complications rate by three folds. Methods: A study was undertaken with 50 diagnosed patients of peptic ulcer disease to predict their morbidity and mortality using risk stratified Boey Score. Results: Perforated peptic ulcer is more common in males with younger age group and risk significantly increases with increase in Boey score. Pulmonary complications are commonest followed by surgical site infection. The accuracy in predicting morbidity and mortality with Boey score was 88.70%and 84.90% respectively. Conclusions: Boey score is a simple and precise predictor of post-operative status of the patients with perforated peptic ulcer patients. Pre-operative prediction with Boey score goes a long way in reducing mortality and morbidity and requires timely management with aggressive treatment in such stratified high risk patients.